2003
DOI: 10.1097/01.tp.0000041702.31262.cd
|View full text |Cite
|
Sign up to set email alerts
|

Long-term mycophenolate mofetil monotherapy in combination with calcineurin inhibitors for chronic renal dysfunction after liver transplantation

Abstract: Our cohort with prolonged follow-up showed significant improvement in renal function with both MMF monotherapy and in combination with low-dose CNI with minimal rejection (five of six steroid responsive) and no graft loss. MMF substitution is a therapeutic strategy that deserves more extensive use in liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 8 publications
3
58
0
1
Order By: Relevance
“…Previous reports support the use of MMF in the management of patients (14)(15)(16)(17)19) with CNI-related CRD. In our study of 50 patients with CNI-related CRD, renal function, assessed by serum creatinine, blood urea nitrogen and creatinine clearance levels improved during the entire followup period after CNI dose reduction or withdrawal and MMF introduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports support the use of MMF in the management of patients (14)(15)(16)(17)19) with CNI-related CRD. In our study of 50 patients with CNI-related CRD, renal function, assessed by serum creatinine, blood urea nitrogen and creatinine clearance levels improved during the entire followup period after CNI dose reduction or withdrawal and MMF introduction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports support the use of MMF in combination with CNI reduction (14)(15)(16)(17) or withdrawal (16,(18)(19) in the management of patients with CNI-related chronic renal dysfunction (14)(15)(16)(17) with good results in terms of improvement of renal function. However, there are few reports on CNI withdrawal and MMF monotherapy, and these were in small series with a short follow up (16,(18)(19). In the present study, we report our experience with CNI withdrawal and MMF monotherapy in liver transplant recipients with CNIrelated toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published report from the Royal Free Hospital in London has proposed another possible course of action. 7 They reported on 45 patients with CKD after OLT. One group of stable patients an average of 31 months post-OLT were converted to MMF monotherapy.…”
Section: Commentsmentioning
confidence: 99%
“…In liver transplantation, introduction of MMF as monotherapy resulted in an improvement in renal function, even when introduced several years after transplantation (Moreno et al, 2003b;Papatheodoridis et al, 1999;Raimondo et al, 2003;Moreno et al, 2003a). However, some reports demonstrated that the risk of acute rejection may increase with an incidence ranging between 18% and 20% (Schlitt et al, 2001;Stewart et al, 2001).…”
Section: Mmf and Immunosuppressive Drug Combinations In Solid Transplmentioning
confidence: 99%